1985
DOI: 10.2170/jjphysiol.35.495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ca2+ on the decay of rhodopsin photoproducts and photoreceptor adaptation in the isolated bullfrog retina.

Abstract: Relationships between the change in threshold of the fast PIII response and the rhodopsin photoproduct content were studied in the isolated bullfrog retina treated with Ba2+ and aspartate. A reduction in the extracellular Ca2+ concentration from 1.0 to 0.01 mM caused an increase in the decay rate of 380 nm absorbing photoproducts (metarhodopsin II and retinal) and metarhodopsin III. In both normal and low Ca2+ solutions, the threshold change after bleaching of about 50% of rhodopsin was closely related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recently, ALBERT et al (1984) have suggested that rhodopsin stabilizes the bilayer structure of the disc membrane and Ca2+ destabilizes it. In addition, HANAWA et al (1985) demonstrated that the decay rate of rhodopsin intermediates increased by immersing the isolated retina in 0.01 mM Ca2+ solution. Considering the results mentioned, it appears likely that when photoreceptors are exposed to low levels of Ca2+ or papaverine, conformational changes of the disc membrane in the outer segment are produced by bleaching of rhodopsin, resulting in a decrease of the releasing rate of the internal transmitter from the disc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ALBERT et al (1984) have suggested that rhodopsin stabilizes the bilayer structure of the disc membrane and Ca2+ destabilizes it. In addition, HANAWA et al (1985) demonstrated that the decay rate of rhodopsin intermediates increased by immersing the isolated retina in 0.01 mM Ca2+ solution. Considering the results mentioned, it appears likely that when photoreceptors are exposed to low levels of Ca2+ or papaverine, conformational changes of the disc membrane in the outer segment are produced by bleaching of rhodopsin, resulting in a decrease of the releasing rate of the internal transmitter from the disc.…”
Section: Discussionmentioning
confidence: 99%